Analisis Kualitas Pelayanan Dengan Menggunakan Metode Servqual (Studi Kasus Internet Service Provider PT Giandra Saka Media) - Gilang Bhirawa Noraga; Dadang Sudirno; Hani Sri Mulyani (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2024)
Customer satisfaction is something that is very important for service companies. This research aims to measure customer satisfaction with the Internet Service Provider PT Giandara Saka Media (Gisaka Media). The method used in this research is the Servqual method and the Cartesian diagram model. In general, the quality of service at the Internet Service Provider PT Giandara Saka Media (Gisaka Media) still does not fully meet customer expectations, because the gap value for each dimension is still negative (-), the largest gap is in the Assurance Dimension and the smallest is in the Empathy dimension. The Assurance dimension must be given special attention in improving services, especially services in terms of guarantees that services will run without significant disruption, guarantees of suitability of services to what is advertised and compliance with contracts with customers and network availability. If ISPs want to develop further and still be able to retain existing customers, then service quality in all dimensions must be immediately improved, especially in the assurance dimension